Synergistic catalytic effects of ZIF-67 and transition metals (Ni, Cu, Pd, and Nb) on hydrogen storage properties of magnesium. (5th May 2020) - Wang, Yongqing; Lan, Zhiqiang; Fu, Hong; Liu, Haizhen; Guo, Jin
Abstract: MgTM/ZIF-67 nanocomposites were prepared by the deposition-reduction method using ZIF-67, MgCl2, and TMCl x (TM = Ni, Cu, Pd, Nb) as raw materials. The dehydrogenation activation energies of MgTM/ZIF-67 (TM = Ni, Cu, Pd, Nb) nanocomposites were calculated to be 115.4 kJ mol −1 H2, 115.7 kJ mol −1 H2, 113.6 kJ mol −1 H2, and 75.8 kJ mol −1 H2, respectively; hence, the MgNb/ZIF-67 nanocomposite manifested the best comprehensive hydrogen storage performance. The hydrogen storage capacity of the MgNb/ZIF-67 nanocomposite was hardly attenuated after the 100th hydrogen absorption-desorption cycle. The dehydrogenated enthalpies of MgH2 and CoMg2 H5 in MgNb/ZIF-67 hydride were calculated to be 72.4 kJ mol −1 H2 and 81.0 kJ mol −1 H2, respectively, which were lower than those of additive-free MgH2 and Mg/ZIF-67. The improved hydrogen storage properties of MgNb/ZIF-67 can be ascribed to the CoMg2 –Mg(Nb) core-shell structure and the catalytic effects of NbH and niobium oxide nanocrystals. Graphical abstract: Image 1 Highlights: The MgTM/ZIF-67 (TM = Ni, Cu, Pd, Nb) nanocomposites were prepared. MgNb/ZIF-67 shows excellent dehydrogenation kinetic property. CoMg2 –Mg(Nb) core-shell plays a buffer role to improve cyclic stability. The NbH and niobium oxide nanocrystalline in MgNb/ZIF-67 act as catalysts.